The divisive character of public works programmes - Cseh-Papp, Imola (Studia Mundi – Economica, 2018)
Among the tools of labour market, public works is one of the oldest; therefore its use is almost natural. Although at the same time it is the aim of public works, the extent and targetedness of its use which decide whether public works functions as an active tool of employment policy or rather as a socio-political tool to manage poverty. Connecting welfare to public works (workfare) can only be understood related to reintegration efforts aiming at the unemployed and also to fighting poverty. The aim of reintegrating programmes is to support the permanent unemployed and other underprivileged groups to return to labour market. The principle of public works in Hungarian practice is: „work instead of social benefit”. The question is whether public works is a relevant and professionally supportable tool in the long run for those who are interested or something else might prove more efficient. The study presents the issue of this dichotomy. The actuality of the chosen topic is given by the fact that the amount the national resource spent on public works has almost quintupled since 2010.